William Hughes, That Devil's Trick: Hypnotism and the Victorian Popular Imagination. Manchester: Manchester University Press, 2015 (2018), 256 pp. Hb £70, ISBN: 978-0719074837; Pb £15.99 ISBN: 978-1-5261-2714-3. Issue 1 (2019) - Crofts, Matthew
No abstract available